Special features of nursing of patients treated by narcotic medications - Jermolajava, Tatjana; Valiulienė, Žaneta (Slauga. Mokslas ir praktika, 2020)
For a long period narcotic medications are widely used for the relief of acute and chronic cancer pain, and nowadays they are also used for pain management in non-cancer patients and patients with chronic diseases. Special features of nursing of supportive care and nursing hospital patients treated with narcotic medications are under-studied. With the increase of incidence problems of communication between patients and nurses arise more frequently causing unsuitable nursing and help for patients in need. This research was conducted on October 12th-19th, 2015. Permission of the Supportive Care and Nursing Hospital was obtained before start of the survey. Twenty four nurses of the Supportive Care and Nursing Hospital who participate in care of patients receiving narcotic medications participated in the survey. It showed that nurses working in the Supportive Care and Nursing Hospital have a sufficient knowledge about narcotic medications. Survey participants gain their knowledge about use of narcotic medications for treatment mostly at conferences, workshops and medical literature. The most frequent reported complaints of patients taking narcotic medications is neurotoxic effects, pain, constipation, low effectiveness of analgesics, nausea and vomiting, and only minority of patients believe that it is physical addiction. Research show that nurses should also help patient to maintain their respiratory function. It is arguably that nursing of every patient shall be individual and adjusted according to presently existing nursing needs of patient on treated with narcotic medications.